Global Health Simulation During Residency. (12th August 2016) - Rosenman, Jane R.; Fischer, Philip R.; Arteaga, Grace M.; Hulyalkar, Manasi; Butteris, Sabrina M.; Pitt, Michael B.
Resident participation in international health electives (IHEs) has been shown to be beneficial, yet not all residents have the opportunity to participate. We sought to determine whether participating in simulated global health cases, via the standardized Simulation Use for Global Away Rotations (SUGAR) curriculum, was useful for all pediatric residents, not merely those planning to go on an IHE. Pediatric residents in our program took part in 2 SUGAR cases and provided feedback via an online survey. Thirty-six of 40 residents participated (90%); 72% responded to the survey. Three of 10 residents not previously planning to work in resource-limited settings indicated participation in SUGAR made them more likely to do so. Nearly all residents (88%) felt SUGAR should be part of the residency curriculum. All felt better prepared for working cross-culturally. While designed to prepare trainees for work in resource-limited settings, SUGAR may be beneficial for all residents.